Anticorruption as transnational law: The Foreign Corrupt Practices Act, PRC law, and party rules in China - Erie, MS (Oxford University Press, 2019)
Corruption has been linked to urgent transnational problems, including, inter alia, market uncertainties, the undermining of democracy, economic disparity, religious extremism, and authoritarianism. As corruption is a global problem, it requires coordination across states’ anticorruption laws. Anticorruption thus provides grounds to reassess the promise and limits of transnational law. This Article examines the operation of anticorruption as transnational law across the corporate governance regimes of the United States and China, the world’s two largest economies. As opposed to perceptions that Washington and Beijing are engaged in a zero-sum game, anticorruption is a policy concern against which both states may rally. Inter-regulatory coordination is far from a frictionless process, however. Cross-border lawyers working on both sides of the Pacific engaged in anticorruption law are a type of transnational community and highlight these tensions. Lawyers apply standards in the 1977 U.S. Foreign Corrupt Practices Act, the People’s Republic of China antibribery laws, and internal Chinese Communist Party rules to ensure their clients comply with multiple regimes. Ethnographic data shows that lawyers assess different regulatory environments, in this case, one of extraterritorial jurisdiction and the other characterized by a political campaign, in the course of advising multinational companies. The Article argues that lawyers’ roles are a lynchpin of these overlapping systems of compliance as their work operates to discipline corporations in China; nonetheless, lawyers’ position in the global legal market impacts what they deem to be “corrupt” and which rules apply. A focus on cross-border lawyers as transnational communities thus marries legal analysis with a contextual grounding in lawyers’ work, an approach that has merit for the study of comparative law more generally. The Article finds that given market pressures, in the area of anticorruption, trends show a preference for “bicultural lawyers,” those who are both embedded within transnational communities and respond to demands in the global market.